A Dose-Dependent Effect of Carnipure(R)Tartrate Supplementation on Endurance Capacity, Recovery, and Body Composition in an Exercise Rat Model - Şahin, Kazım; Orhan, Cemal; Küçük, Ömersman; Şahin, Nurhan; Tuzcu, Mehmet; Er, Besir; Bellamine, Aouatef (Mdpi, 2020)
The objective of this work is to investigate the effects of Carnipure(R)Tartrate (CT) supplementation with or without exercise on endurance capacity, recovery, and fatigue by assessing time to exhaustion as well as body weight and composition in rats. In addition, antioxidant capacity has been evaluated by measuring malondialdehyde (MDA) levels and antioxidant enzyme (superoxide dismutase, SOD; catalase, CAT; glutathioneperoxidase; GSHPx) activities. Fifty-six male Wistar rats were divided into eight groups including seven rats each. A control group did not receive CT nor exercise. Another control group received 200 mg/kg CT without exercise. The other six groups of rats went through an exercise regimen consisting of a 5-day training period with incremental exercise capacity, which was followed by 6 weeks of the run at 25 m/min for 45 min every day. CT was supplemented at 0, 25, 50, 100, 200, and 400 mg/kg per day during the 6 weeks. Rats submitted to exercise and supplemented with CT had a significant and dose-dependent increase in time to exhaustion and this effect seems to be independent of exercise (p< 0.05). Additionally, recovery and fatigue were improved, as shown by a significant and dose-dependent decrease in myoglobin and lactic acid plasma levels, which are two markers of muscle recovery. CT supplementation led to a dose-response decrease in body weight and visceral fat. These effects become significant at 200 and 400 mg/kg doses (p< 0.05). Additionally, the antioxidant capacity was improved, as shown by a significant and dose-dependent increase in SOD, CAT, and GSHPx. Serum MDA concentrations decreased in exercising rats with CT supplementation. CT supplementation led to a decrease in serum glucose, triglycerides, and total cholesterol concentrations with the lowest levels observed at 400 mg/kg dose (p< 0.05). These effects correlated with a significant dose-dependent increase in serum total L-carnitine, free L-carnitine, and acetyl-carnitine, which linked the observed efficacy to CT supplementation. These results demonstrate that CT supplementation during exercise provides benefits on exercise performance, recovery, and fatigue as well as improved the lipid profile and antioxidant capacity. The lowest dose leads to some of these effects seen in rats where 25 mg/kg corresponds to 250 mg/day as a human equivalent.
Keywords: L-carnitine; recovery; exercise; endurance; fatigue; body mass index; metabolic parameters